THE INFLUENCE ANALYSIS OF INTEGRATED MARKETING COMMUNICATION MIX ON CONSUMER PURCHASING DECISION - STUDY CASE OF PT. MULTI CITRA ABADI - Sualang, Fiano Dendi (Sam Ratulangi University, 2015)
ABSTRACT Nowadays, every company has their own marketing strategy to survive in market competition, but sometimes the marketing communication campaign was out-of-date and the improvement comes slow. Moreover, marketing methods were not efficient, because most of the consumer does not know about the products or even the companyâ€™s profile. According that, the company should have to improve and have an appropriate marketing communication strategy. The aim of this research is to analyze the influence of integrated marketing communication mix on consumer purchasing decision. The case study of this research is PT. Multi Citra Abadi as known as Multimart. The population is Manado people who have an experience purchasing in Multimart. The sample is taken by 100 respondents. Result shows Advertising, Public Relation, Personal Selling, Sales Promotion and Direct Marketing have significant influence on Consumer Purchasing Decision. The company should pay more attention on integrated marketing communication strategy to increase sales. Â Keywords: Integrated Marketing Communication, Advertising, Public Relation, Personal Selling, Sales Promotion, Direct Marketing, Consumer Purchasing Decision